Kerjasama Korea Selatan –Indonesia dalam Manajemen Bencana Alam (Rekontruksi Aceh Pasca Tsunami Samudera Hindia) - Ady Muzwardi (Department of International Relations, Universitas Andalas, 2016)
Natural Distasters is a part of media diplomacy and cooperation between nations, strengthening disaster preparedness for effective response at all levels. In coping with disasters, national resources could be overwhelmed, especially in the event of large-scale disasters. In this respect, bilateral and regional cooperation is of particular importance, and this is part of the Korean Indonesian relations. The political dialogue also intends to foster closer cooperation on humanitarian and activities between the Indonesia and Korean. The tsunami in Aceh serves as an example of media diplomacy between the two nations as part of global cooperation. The development of political, social and culture cooperation through reconstruction efforts, programs and projects in Aceh has become a strength in the diplomatic relations between South Korea and Indonesia. This research aims to share knowledge and exchange best practices and to be able to work together in the event of major disasters. . Keywords:Natural Disasters, diplomacy, reconstruction.